2002
DOI: 10.1080/000163502753740160
|View full text |Cite
|
Sign up to set email alerts
|

Third molar agenesis in Down syndrome

Abstract: The frequency, gender, and maxillary/mandibular occurrences of third molar agenesis have been studied in a Danish population of Down syndrome individuals (39 F and 31 M). The study was based on radiological examination and compared with 2 control groups of normal Caucasian populations. We found that the occurrence of third molar agenesis in Down syndrome individuals was around 4 times greater than in a normal population and higher than in corresponding previous studies. The agenesis occurred more often in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…40 The reported prevalence of third molar agenesis in DS is much higher. It was noted in 88% of our sample, similar to the 84.4% reported by Lomholt et al 20 from Denmark but greater than the 74% reported by Shapira et al 19 from Israel. Agenesis of all third molars was seen in 52% of our sample, similar to the 55% reported by Shapira et al 19 Because of the frequent agenesis of all third molars in our sample, we explored whether this occurrence was associated with any specific craniofacial features.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…40 The reported prevalence of third molar agenesis in DS is much higher. It was noted in 88% of our sample, similar to the 84.4% reported by Lomholt et al 20 from Denmark but greater than the 74% reported by Shapira et al 19 from Israel. Agenesis of all third molars was seen in 52% of our sample, similar to the 55% reported by Shapira et al 19 Because of the frequent agenesis of all third molars in our sample, we explored whether this occurrence was associated with any specific craniofacial features.…”
Section: Discussionsupporting
confidence: 75%
“…Most studies report that mandibular second premolars, maxillary lateral incisors, maxillary second premolars, and mandibular central incisors are the teeth most often affected (in decreasing order). 35 In DS, the prevalence of hypodontia is much greater and more severe [12][13][14][15][16][17][18][19][20][21][22] and is recognized as a characteristic phenotypical feature of the syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 • Reassure parents that delayed and irregular dental eruption patterns are common and that hypodontia occurs with increased frequency (23%). 77,78 • Encourage and model use of accurate terms for genitalia and other private body parts (penis, vulva) any time these body parts are discussed or examined. Model respect for body rights by reminding patients that their body is their own and explain to the child what you will do before moving into child's personal space or performing a procedure.…”
Section: Anticipatory Guidancementioning
confidence: 99%